Immediate and longitudinal effects of maltreatment on systemic inflammation in young children. (December 2020) - Entringer, Sonja; de Punder, Karin; Overfeld, Judith; Karaboycheva, Gergana; Dittrich, Katja; Buss, Claudia; Winter, Sibylle Maria; Binder, Elisabeth B.; Heim, Christine
Abstract: Exposure to child maltreatment increases the risk for psychiatric and physical diseases. Inflammation has been proposed as a mechanism through which early adverse experiences become biologically embedded. However, most studies providing evidence for the link between early adverse exposures and inflammation have been retrospective or cross-sectional in design, or did not assess inflammation immediately after maltreatment in young children. In the present study we investigated the association between childhood maltreatment and salivary C-reactive protein (CRP) concentrations in a population of N = 173 children, 3–5 years of age, who were recruited in the immediate aftermath of maltreatment and followed-up longitudinally every 6 months over a period of 2 years. We found that the association between maltreatment and CRP concentrations was significantly moderated by child sex, such that in girls, CRP concentrations were higher in the maltreated compared to the control group, and this difference was stable across the 2-year follow-up-period, while in boys, there was no association between maltreatment and CRP. Our findings suggest that the effect of maltreatment on inflammation may already emerge right after exposure at a very young age in girls and manifest over time. Our study provides important evidence for the development of personalized, early interventions strategies targeting the early-life period.